2010
DOI: 10.1016/j.bbr.2010.01.022
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT7 receptor as a mediator and modulator of antidepressant-like behavior

Abstract: The 5-HT 7 receptor has been suggested as a target for treating depression since inactivation or blockade of the receptor has an antidepressant-like behavioral effect. The present study investigated possible interactions between various classes of drugs with antidepressant properties and blockade or inactivation of the 5-HT 7 receptor. Immobility despair in the tail suspension test and the forced swim test was evaluated in mice lacking the 5-HT 7 receptor (5-HT 7 −/− ) and in wild-type controls (5-HT 7 +/+ ) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
90
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 67 publications
2
90
0
3
Order By: Relevance
“…Additionally, Abbas et al (2009) demonstrated that, in contrast to their wild-type littermates, 5-HT 7 receptor knock-out mice did not respond to amisulpride in the FST and the tail suspension test. This indicates that 5-HT 7 receptor antagonism may underly, at least in part, the antidepressant-like actions of antipsychotics such as amisulpride and aripiprazole (Abbas et al, 2009;Sarkisyan et al, 2010). Taken together, these data suggest that 5-HT 7 receptor antagonists are of potential interest for the treatment of both depression and anxiety.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, Abbas et al (2009) demonstrated that, in contrast to their wild-type littermates, 5-HT 7 receptor knock-out mice did not respond to amisulpride in the FST and the tail suspension test. This indicates that 5-HT 7 receptor antagonism may underly, at least in part, the antidepressant-like actions of antipsychotics such as amisulpride and aripiprazole (Abbas et al, 2009;Sarkisyan et al, 2010). Taken together, these data suggest that 5-HT 7 receptor antagonists are of potential interest for the treatment of both depression and anxiety.…”
Section: Discussionmentioning
confidence: 87%
“…This group reported that an intrahippocampal injection of SB-269970 also reduces immobility time, suggesting that the hippocampus is one of the brain structures involved in the beneficial action of 5-HT 7 antagonism (Wesolowska et al, 2006). It has also been reported that both pharmacological inhibition and genetic inactivation of 5-HT 7 receptors induce antidepressant-like behavior in the mouse tail suspension test (Hedlund et al, 2005;Bonaventure et al, 2007;Sarkisyan et al, 2010), as well as an antianxiety effect in the Vogel drinking test in rats, the elevated plus maze in rats, and in the four-plate test in mice (Wesolowska et al, 2006). Interestingly, a dose of 2 mg/kg of SB-269970 had no detectable effect in the present study by itself, suggesting a lack of modification of 5-HT release as previously shown (Bonaventure et al, 2007), it counteracted the anxiogenic-like effect of acute administration of fluoxetine in the illuminated open field (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] In particular, several of the compounds listed in Table 1 are effective antidepressants, and in animal models, the antidepressant efficacy of aripiprazole is reversed in animals lacking 5-HT 7 receptors, 8 and the serotonin release and antidepressant actions of selective serotonin reuptake inhibitors (SSRIs) are enhanced by selective 5-HT 7 antagonists. 3,5,8 Three novel agents characterized as antipsychotics have 5-HT 7 antagonist properties among their most potent pharmacologic actions ( Figure 1), 2,10,13,14 and 1 of these, lurasidone, in late-stage clinical development as an antipsychotic, is actually "5-HT 7 preferring, " with 5-HT 7 antagonism its most potent property. 13 Of these, amisulpride (not available in the United States) is a proven antidepressant.…”
Section: -Ht 7 Receptors As Novel Therapeutic Targetsmentioning
confidence: 99%
“…[3][4][5]8 Given the recent positive results as an antidepressant for the melatonergic/ serotonergic agent agomelatine, which resets circadian rhythms, 18 combining novel 5-HT 7 antagonists with melatonin agonism may also enhance the antidepressant actions of 5-HT 7 antagonists. In addition, preclinical studies 3,5,8,9 suggest the possibility that agents with potent 5-HT 7 antagonism may improve cognition, so cognition in depression, schizophrenia, and other illnesses is a theoretically attractive clinical target, for 5-HT 7 antagonists as well. …”
Section: -Ht 7 Receptors As Novel Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation